Lack of investigation 2001-2007: incidents reported to the Health and safety Executive (London, 2008)
"This report examines incidents reported to and investigated by HSE over a six year period (2001/2 and 2006/7). It examines levels of investigation - numbers and rates - of major injuries, over three day injuries, injuries to the public and dangerous occurrences. It breaks this examination down to look at the levels of investigation by year, sector, region, kind of injury (or dangerous occurrence) and cause of injury. The issue of investigation levels - the central concern of this report - is a crucial one, because unless the HSE investigates an incident, it cannot know whether the injury or dangerous occurrence was caused by a health and safety failure."